The Effect of Solvency Ratio on Profitability Ratio in PT. Unilever Tbk Period 2014-2021 - Idris, Abdi Akbar; Hasbiah, Siti (PT. Maju Malaqbi Makkarana, 2023)
This study aims to determine the influence of the solvency ratio has an influence on the ratio at PT. Unilever Tbk for the 2014-2022 quarter, the data in this study are secondary data for 32 samples. The methods used to analyze the relationship between variables are descriptive analysis, classical assumption test, multiple linear regression and hypothesis testing. The findings in this study show that partially the solvency ratio has no effect on the solvency ratio. It is also known that the solvency ratio does not have a significant effect on changes in earnings